2013
DOI: 10.1159/000350322
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of the Hedgehog Signalling Pathway in Head and Neck Squamous Cell Carcinoma

Abstract: Background: Overexpression of the Hedgehog (HH) signalling pathway has been described in several malignancies and is associated with a poor prognosis. HH signalling blockade reduces tumour growth in vitro and in vivo. We aimed to determine whether head and neck squamous cell carcinomas (HNSCCs) express HH proteins in comparison to healthy mucosa. Patients and Methods: Formalin-fixed and paraffin-embedded tissue sections of 10 patients with HNSCC were stained with fluorescence-labelled antibodies for cytokerati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 36 publications
1
10
0
Order By: Relevance
“…Promisingly, RT-PCR confirmed the increase of GLI1 expression levels in HNSCC tumors over normals and RNA-seq from TCGA confirmed higher GLI1 expression in HPV-negative samples. The increased expression of GLI1 in HNSCC tumors in this study is consistent with observed GLI1 overexpression in HNSCC [24], [42], [43] and our previously published data showing that high expression of nuclear GLI1 is associated with poor survival and distant metastasis [24].…”
Section: Discussionsupporting
confidence: 93%
“…Promisingly, RT-PCR confirmed the increase of GLI1 expression levels in HNSCC tumors over normals and RNA-seq from TCGA confirmed higher GLI1 expression in HPV-negative samples. The increased expression of GLI1 in HNSCC tumors in this study is consistent with observed GLI1 overexpression in HNSCC [24], [42], [43] and our previously published data showing that high expression of nuclear GLI1 is associated with poor survival and distant metastasis [24].…”
Section: Discussionsupporting
confidence: 93%
“…[ 19 20 ] Image analysis in red, green, blue (RGB) mode provided objective evidence for over-expression of Hh signaling components in head and neck squamous cell carcinoma (HNSCC), particularly with regard to the transcription factors gli1 (10-fold) and sonic Hh (SHH) (5-fold) in comparison with healthy mucosa. [ 21 ]…”
Section: Introductionmentioning
confidence: 99%
“…At first glance, this finding seems to be contradictory because significant overexpression of Shh was detected in Gal3 +/+ mouse lesions, which might indicate increased Hh signaling pathway upregulation in this group when compared with Gal3 −/− mice. However, Gli3 expression is not always accompanied by uncontrolled Hh signaling activity and one recent study showed higher Gli3 expression in healthy mucosa than in head and neck carcinoma samples (Dimitrova et al, 2013). It is well known that Gli3 contains C-terminal activation and N-terminal repressor domains, which allows it to have a dual role in the Hh pathway under influence of the Hh ligand and its proteolytic processing after Sufu-GSK-3b-mediated phosphorylation (Amakye et al, 2013;Briscoe and Therond, 2013;Kise et al, 2009).…”
Section: Discussionmentioning
confidence: 99%